2000
DOI: 10.2190/bg2m-a5er-kv7y-n0j5
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Computer Use in an Academic Institution: Report from a Longitudinal Study

Abstract: This article explores the nature of the relationships between gender, categories of computer use, and attitudes toward computers in a computer enriched environment where all students were provided with network access and laptop computers over a four-year period. The results indicate that women were less positive about computers than men, and the use level of computers by women were less frequent than for men. This change in the relationship is a throwback to the earlier days of computing when research had indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 22 publications
3
44
0
Order By: Relevance
“…These Indicates statistical difference at P < 0.01. discrepancies in the literature could relate to study design, the type of intervention, and the students (e.g., residents vs. medical students). Our observation that gender was associated with CAI use was not entirely surprising in view of literature demonstrating a link between gender and computer use in general (Mitra et al, 2000;Ames, 2003). In contrast to the more prevalent view that males have more positive attitudes and use computers more often (Whitley, 1997;Kay, 2006), we found that medical student females tended to use CAI resources more frequently.…”
Section: Discussionsupporting
confidence: 44%
“…These Indicates statistical difference at P < 0.01. discrepancies in the literature could relate to study design, the type of intervention, and the students (e.g., residents vs. medical students). Our observation that gender was associated with CAI use was not entirely surprising in view of literature demonstrating a link between gender and computer use in general (Mitra et al, 2000;Ames, 2003). In contrast to the more prevalent view that males have more positive attitudes and use computers more often (Whitley, 1997;Kay, 2006), we found that medical student females tended to use CAI resources more frequently.…”
Section: Discussionsupporting
confidence: 44%
“…Such differences have sometimes been attributed to a propensity for males to have greater experience with using computers [48,49]. However, in the current study all participants had similar computer and Web experience since the majority of them were self-identified as experienced users apart from 2 females and 4 males.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, female and male students are likely to be different in terms of the types of computer use rather than in all areas of ICT application (Colley, 2003;Mitra et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…For example, men and boys are more intensive users of the Internet, enjoy more competitive forms of e-learning, and encounter different problems while using ICT, compared with women and girls (Colley, 2003;Copper & Weaver, 2003;Volman & Eck, 2001;Volman, Eck, Heemskerk, & Kuiper, 2005). Moreover, several investigations indicated that gender gaps probably became more latent and more complex (Colley, 2003;McIlroy, Bunting, Tierney & Gordon, 2001;Mitra, Lenzmeier, Steffensmeier, Avon, Qu & Hazen, 2001). While gender differences in ICT related attitudes and cognitions disappeared at scale level, they seem to persist at factor level (McIlroy et al, 2001).…”
Section: Introductionmentioning
confidence: 99%